Humor in Digital Discourse: A Pragmatic Analysis of Memes on Social Media - Ali, Sri Widyarti; Husain, Nurlaila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aimed to investigate the pragmatic functions of humor employed in memes shared across major social media platforms. Utilizing a qualitative approach grounded in pragmatic analysis, the study explored how users leverage linguistic and visual elements to construct comedic meaning and achieve communicative goals. Drawing from a diverse corpus of popular memes from Facebook, Twitter, Instagram, and Reddit, the analysis identified pragmatic strategies such as incongruity, exaggeration, wordplay, and parody used to create humorous effects. The findings revealed humor's vital roles in facilitating social commentary, subverting dominant narratives, fostering community-building, and negotiating identity. Users deployed sarcasm, hyperbole, and visual metaphors to critique norms, question power structures, and provide platforms for marginalized voices. Furthermore, humor enabled collective processing of shared experiences, fostering camaraderie and mutual understanding. By tapping into contextual factors like intertextual references and shared knowledge, memes resonated with audiences and facilitated the negotiation of collective narratives. The research underscores humor's multifaceted potential in shaping digital discourse, including expression, critique, community formation, and identity construction, highlighting its capacity to empower, connect, and facilitate meaningful dialogue through laughter.